2015
DOI: 10.1123/ijspp.2014-0062
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Microsensors to Automatically Detect Bowling Events and Counts in Cricket Fast Bowlers

Abstract: The bowling-detection algorithm from the MinimaxX device is sensitive to detect bowling counts in both cricket training and competition. Although specificity is high during training, the number of false positive events increased during competition. Additional bowling workload measures require further development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 15 publications
5
57
0
Order By: Relevance
“…That is, of the 245 true-and false-positive collision events ≥2 seconds, 98.4% (n = 241) were true-positive outcomes and 1.6% (n = 4) were false-positive. McNamara et al recently demonstrated that microtechnology: (1) was sensitive to detect bowling counts in cricket fast bowlers, 21 (2) provided a reproducible measure of external workload, 22 and (3) could be used to identify spikes in high-intensity acute:chronic workload ratios. 23 Although the risk of team sport athletes sustaining a contact injury has been associated with poor high-intensity running ability, 24 changes in locomotor distance and acceleration workloads (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…That is, of the 245 true-and false-positive collision events ≥2 seconds, 98.4% (n = 241) were true-positive outcomes and 1.6% (n = 4) were false-positive. McNamara et al recently demonstrated that microtechnology: (1) was sensitive to detect bowling counts in cricket fast bowlers, 21 (2) provided a reproducible measure of external workload, 22 and (3) could be used to identify spikes in high-intensity acute:chronic workload ratios. 23 Although the risk of team sport athletes sustaining a contact injury has been associated with poor high-intensity running ability, 24 changes in locomotor distance and acceleration workloads (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, different activity types can be classified based on the features of the accelerometer signal. McNamara et al (2015) developed a bowling detection algorithm for cricket. The researchers found that the algorithm was able to classify cricket bowling more effectively in training than game-play, with a maximum accuracy of 98.1% (training).…”
Section: Introductionmentioning
confidence: 99%
“…Such technology has been used to detect collisions in rugby league 78,79 fast bowling in cricket, 80 swimming, 81 and cross-country skiing 82 movements. While these studies have used single devices worn on the upper back, other studies have used multiple devices to identify these sport-specific actions.…”
Section: Inertial Sensorsmentioning
confidence: 99%